Towards high-resolution astronomical imaging. Issue 3 (1st June 2019) - Buscher, David; Chowdhury, Nahid; Davies, Ric; Hinkley, Sasha; Hubin, Norbert; Jorden, Paul; Mackay, Craig; Massey, Richard; O'Brien, Kieran; Parry, Ian; Skottfelt, Jesper
Abstract : Craig Mackay reports from a meeting on the future of high-resolution imaging in the visible and infrared. Abstract: Craig Mackay reports from a recent meeting on "The future of high-resolution imaging in the visible and infrared", reviewing the astronomical drivers for development and the technological advances that might boost performance.